Laser Ablation From Fundamentals to Applications - Itina, Tatiana E. (IntechOpen, 2017)
Shortly after the demonstration of the first laser, the most intensely studied theoretical topics dealt with laser-matter interactions. Many experiments were undertaken to clarify the major ablation mechanisms. At the same time, numerous theoretical studies, both analytical and numerical, were proposed to describe these interactions. These studies paved the ways toward the development of numerous laser applications, ranging from laser micro- and nanomachining to material analysis, nanoparticle and nanostructure formation, thin-film deposition, etc. Recently, more and more promising novel fields of laser applications have appeared, including biomedicine, catalysis, photovoltaic cells, etc. This book intends to provide the reader with a comprehensive overview of the current state of the art in laser ablation, from its fundamental mechanisms to novel applications.